Biofuel for vehicle use in China: Current status, future potential and policy implications. (February 2018) - Hao, Han; Liu, Zongwei; Zhao, Fuquan; Ren, Jingzheng; Chang, Shiyan; Rong, Ke; Du, Jiuyu
Abstract: Biofuel is considered to be a promising solution to the energy and environmental challenges in the transport sector. However, there are few studies focusing on the current status, future potential, policy framework, barriers and opportunities of biofuel development in China, these are analyzed in this study. This study finds that China has been promoting biofuel commercialization with multiple measures, including framing national strategy, initiating demonstration programs, providing financial incentives, and establishing national standards. However, due to technology and market barriers, the actual commercialization scale is far lower than previously projected. Accordingly, it is recommended that the development of non-plantation resource-based biofuel should be given high priority, while plantation resource-based biofuel should be developed with caution. Meanwhile, technology innovation for increasing production efficiency and reduce cost is essential for strengthening biofuel market competitiveness. Subsequently, mandatory legal and policy system for regulating the biofuel industry in China should be established, which can effectively engage different stakeholders in promoting biofuel development. Regarding fuel ethanol, the trade price between the fuel ethanol producers and the oil companies should be further adjusted. As for biodiesel, the illegal utilization of waste oil should be strictly prohibited, which can help to increase the feedstock supply, as well as bring down the price. Last but not the least, the financial incentives for biofuel production should also be optimized.